Type 2 Diabetes Risk Among Older Asian, Native Hawaiian and Pacific Islander Patients With Head and Neck Cancer in the United States - Chun‐Pin Esther Chang; Sarah M. Drejet; Jason P. Hunt; Marcus Monroe; Mia Hashibe (Cancer Medicine, 2026)
ABSTRACT Diabetes is one of the most prevalent comorbidities among patients with head and neck cancer (HNC), and its burden is disproportionately higher in Asian American, Native Hawaiian, and Pacific Islander (ANHPI) populations. However, the incidence and risk factors for diabetes among ANHPI HNC patients remain unknown. The aim of our study was to examine the incidence and risk factors of developing Type 2 diabetes among older (≥ 66 years of age) ANHPI HNC patients in the United States, as well as differences across ANHPI subgroups. Using the SEER‐Medicare linked database, we identified Non‐Hispanic White (NHW) and ANHPI patients diagnosed with HNC from 2000 to 2019. Fine‐Gray subdistribution hazard models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for diabetes among ANHPI subgroups compared to three reference groups: NHW, East Asian, or Chinese HNC patients. The study included 2862 older NHW, 423 East Asian, 211 Southeast Asian, 139 South Asian, and 68 NHPI HNC survivors. South Asian HNC survivors had the highest incidence of Type 2 diabetes (19.4%) compared to other ANHPI subgroups (7%–14%) and non‐Hispanic White (NHW) HNC survivors (7.5%) > 1 year after cancer diagnosis. East Asian (HR: 2.04; 95% CI: 1.36, 3.06; incidence: 14.0%) and South Asian (HR: 3.34; 95% CI: 1.86, 6.00) HNC survivors had higher diabetes risks compared to NHW HNC survivors > 1 year after cancer diagnosis, notably among Chinese and Asian Indian/Pakistani HNC survivors. Our results showed a 2‐ to 3‐fold difference in risk of Type 2 diabetes for ANHPI HNC survivors compared to NHW HNC survivors. There was a high incidence of diabetes, especially in the South and East Asian HNC patients, highlighting the need for prevention in these groups. Small sample sizes among ANHPI subgroups with fewer than 100 HNC patients (Korean, Vietnamese, NHPI) warrant cautious interpretation of these findings.